Relationship of Sleep Quality with Quality of Life in Chronic Kidney Failure Patients Undergoing Hemodialization During the Covid-19 Pandemic - Ulinnuha, Lu'lu' Luthfiatun; Trishinta, Sirli Mardianna; Rosdiana, Yanti (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2022)
Introduction : Poor sleep quality is often experienced by patients with chronic kidney failure (CKD) undergoing hemodialysis (HD) therapy, this can affect their quality of life. The purpose of this study was to determine the relationship between sleep quality and quality of life in chronic kidney failure patients undergoing hemodialysis during the COVID-19 pandemic at Panti Waluya Sawahan Hospital, Malang City. Method : This research design is cross sectional. The population in this study were patients with chronic kidney failure who underwent hemodialysis, namely 126 respondents at Panti Waluya Sawahan Hospital, Malang City during January, obtained a sample of 36 respondents using purposive sampling technique. Data collection techniques used the Pittsburgh Sleep Quality Index (PSQI) questionnaire and The World Health Organization Quality of Life (WHOQOL – BREF) questionnaire. Data analysis used Chi Square test (p value < 0.05). Result : The results of the study, most of the respondents had poor sleep quality and most of the respondents had poor quality of life. The results of the chi square test showed that there was a relationship between sleep quality and quality of life in chronic kidney failure patients undergoing hemodialysis during the COVID-19 pandemic at Panti Waluya Sawahan Hospital, Malang City with a p-value of 0.000. Conclusions : The conclusion of this study is that there is a relationship between sleep quality and quality of life in chronic kidney failure patients undergoing hemodialysis during the COVID-19 pandemic at Panti Waluya Sawahan Hospital, Malang City